2000
DOI: 10.1007/s001980070081
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density in the Long Term after Liver Transplantation

Abstract: Hepatic osteodystrophy is a complication of chronic liver disease and bone mass is known to decline further in the first year after liver transplantation. The present study focused on bone mineral density (BMD) between 1 and 15 years after liver transplantation under a prednisolone- and azathioprine-based immunosuppressive regimen. Three groups of adult patients were studied: group 1, 45 patients with a follow-up of 5-9 years after transplantation, had BMD measurements done at 1, 2 and 5 years after transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 5 publications
5
39
2
Order By: Relevance
“…These patients suffered even more fracturing in the first year after OLT, especially in sites of trabecular bone, as has been previously described in other populations of liver transplant recipients. 3,[26][27][28] The incidence and timing of fracturing in patients with ALD, and to a lesser extent HCVϩALD, is very different. Before OLT, patients with ALD had the least osteopenia but a much higher incidence of fracturing than patients with HCV (31% versus 12%).…”
Section: Discussionmentioning
confidence: 99%
“…These patients suffered even more fracturing in the first year after OLT, especially in sites of trabecular bone, as has been previously described in other populations of liver transplant recipients. 3,[26][27][28] The incidence and timing of fracturing in patients with ALD, and to a lesser extent HCVϩALD, is very different. Before OLT, patients with ALD had the least osteopenia but a much higher incidence of fracturing than patients with HCV (31% versus 12%).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15] Most of these fractures occurred in the spine; however, since in some of these studies spinal X-rays were not routinely performed, the true number of vertebral fractures is likely to have been underestimated. In some studies, however, lower fracture rates have been reported.…”
Section: Incidence Of Fragility Fractures After Transplantationmentioning
confidence: 99%
“…In a smaller study of 28 patients, spine bone mineral density had returned to pre-transplantation levels by a mean of 85 months. 27 However, Monegal et al 15 reported recovery of bone mineral density in the spine but not the proximal femur by 36 months after transplantation and Hamburg et al 14 found that recovery of bone mineral density was often incomplete up to 15 years post-transplantation.…”
Section: Changes In Bone Mineral Density After Liver Transplantationmentioning
confidence: 99%
“…51 Interestingly, bone recovery continues for up to 2 to 7 years after transplantation. [52][53][54] Crosbie et al 55 reported that accelerated bone loss in the transplant setting is caused by more bone resorption exceeding bone formation. Furthermore, calculation of an uncoupling index (osteocalcin-deoxypyridinoline) correlated well with bone mineral density and may serve as a noninvasive means to identify high-risk individuals.…”
Section: Bone Diseasementioning
confidence: 99%